Accountability of Financial Management of the Modern Islamic Boarding School Ta'dib Al-Syakirin Which is a Waqf Body - Yurmaini, Yurmaini; Erliyanti, Erliyanti; Salam, Rangga; Anshari, Khairil (Yayasan Rahmat Islamiyah, 2025)
This study aims to explore financial accountability management at the Waqf-based Modern Islamic Boarding School Ta'dib Al-Syakirin. The research uses a qualitative method with a phenomenological approach. Data were collected through in-depth interviews, observations, and documentation. The results show that financial management is not yet in accordance with WAQF accounting standards, being manually managed in a simple way. The lack of staff understanding of Islamic accounting is the main factor behind the lack of transparency and financial accountability. This study recommends implementing PSAK 112 standards for financial reporting to create transparency and public trust.